2022
DOI: 10.3389/fgene.2022.915911
|View full text |Cite
|
Sign up to set email alerts
|

Nanomaterials in Animal Husbandry: Research and Prospects

Abstract: Anti-inflammatory, antiviral, and anti-cancer treatments are potential applications of nanomaterials in biology. To explore the latest discoveries in nanotechnology, we reviewed the published literature, focusing on co-assembled nanoparticles for anti-inflammatory and anti-tumor properties, and their applications in animal husbandry. The results show that nanoparticles have significant anti-inflammation and anti-tumor effects, demonstrating broad application prospects in animal breeding. Furthermore, pooled ev… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
2

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 83 publications
0
5
0
Order By: Relevance
“…This technology is already widely used in various scientific fields, especially in animal nutrition researches. These additives work to increase the feed's resistance to spoilage, heat and light, and protect it from degradation by proteases and various digestive enzymes (Wang et al, 2022a) by using encapsulation, nutrients can be protected against premature spoilage in the rumen and made available for absorption in the small intestine. This can increase the efficacy of feed additives and improve overall animal health and growth.…”
Section: Nano Size Feed Additivesmentioning
confidence: 99%
See 1 more Smart Citation
“…This technology is already widely used in various scientific fields, especially in animal nutrition researches. These additives work to increase the feed's resistance to spoilage, heat and light, and protect it from degradation by proteases and various digestive enzymes (Wang et al, 2022a) by using encapsulation, nutrients can be protected against premature spoilage in the rumen and made available for absorption in the small intestine. This can increase the efficacy of feed additives and improve overall animal health and growth.…”
Section: Nano Size Feed Additivesmentioning
confidence: 99%
“…Nanotechnology plays an important role in the treatment of animal diseases, including therapy, diagnostics, tissue engineering, vaccine development, and many other areas. The application areas include a wide range of fields such as animal health and production, animal breeding, reproduction, animal nutrition (Wang et al, 2022a).…”
Section: Advantages Of Nano-sized Feed Additivesmentioning
confidence: 99%
“…Szewczyk et al suggested that NPs encapsulating doxorubicin and siRNA could potentially be used to develop new treatment method for canine osteosarcoma [31]. The application of nanomaterials and nanotechnology in animal husbandry is very compelling and has already found applications in animal nutrition, feeding and breeding, and animal welfare, especially with respect to NPs' significant anti-inflammatory and antitumor effects, which greatly improve animal breeding [32].…”
Section: Np Delivery Systemmentioning
confidence: 99%
“…There are several types of nanoparticles which are useful for livestock and their details are presented in Table 2 [24]. These are useful as biocides and veterinary medicines, apart from improving nutrient delivery, boosting reproductive system and facilitating easy transportation of other molecules of nutrients, resulting in a miraculous effect on disease cure, growth and production [27].…”
Section: Utilisation Of Nanotechnology For Livestock Developmentmentioning
confidence: 99%